Quantificação de partículas em área de descarga de grãos de uma cooperativa agroindustrial - Fabre Junior, Nilo (2009)
The literature shows a little about the particulate material generated by the movement of soya beans. Therefore, this paper presents a quantification of total and respirable particulate material in a hopper for discharge of soya beans in an agroindustrial cooperative in the countryside of Parana. It was analyzed the concentrations obtained by gravimetry from total and respirable dust for two points of hopper, and the number of particles produced by equipment count in a counter for fifteen points. In gravimetrical measuring it was obtained 82,4 and 40,3 mg/m3 for total dust for points P6 and P12, respectively and 4,09 and 0,59 mg/m3 for respirable dust for points P6 and P12, respectively. In the samples done in the particle counter the concentration of the fifteen items were about 3,36 and 7,39 mg/m3. The paper presents chemical and biological quantitative analysis for the purpose of characterization of the particulate material. It was analyzed the total silic, with 13.49%, and also some metals, there is a lack of lead and chromium. It was also heterotrophic bacteria with 3.6x108 CFU, molds and yeasts, with 1.6x107 CFU, and was compared with the clean air and with references samples taken from the soil. The particulate material generated in the hopper was taken to the microscope, where were characterized the sizes for the Log-Normal model. The results show the harm, based on values defined by the major government agencies worldwide and references in occupational hygiene. The results are also importants for the collect equipment implementation and material mitigation generation.